Evaluation of the Veterans Affairs Boston Healthcare System Primary Care Nurse Practitioner Residency Program - Bethany A. Croke; Chizoba C. Nwosu; Patricia C. Underwood; Karen Tepper; Amelia Colman; Erin Shea (Nursing Education Perspectives, 2026)
Nurse practitioner (NP) residencies support transition to practice and improve retention. We describe outcomes of a primary care NP residency across four cohorts (2020 to 2024) at the Veterans Health Administration-VA Boston Healthcare System (VA-BHS). Evaluated outcomes include clinical competence, confidence in practice, employment, and retention. All 10 residents achieved competence and significantly greater confidence at graduation compared with 1 month after starting the program ( p < .0001). VA-BHS offered eight residents employment, retaining five of the six hired (83%) 1 year postgraduation. The robust confidence, competence, and retention of graduates uphold evidence that residencies support successful NP transition into practice.